Mechanisms of the destabilized Mach reflection of inviscid oblique detonation waves before an expansion corner. (10th June 2022) - Zhang, Zijian; Liu, Yunfeng; Wen, Chihyung
Abstract: Abstract : The stabilization of oblique detonation waves (ODWs) in an engine combustor is important for the successful applications of oblique detonation engines, and comprehensively understanding the effects of the inviscid reflection of ODWs on their stabilization and the relevant mechanisms is imperative to overall combustor design. In this study, the flow fields of ODW reflections in a space-confined combustor are numerically studied by solving the two-dimensional time-dependent multispecies Euler equations in combination with a detailed hydrogen combustion mechanism. The inviscid Mach reflections of ODWs before an expansion corner are emphasized with different flight Mach numbers, Ma, and different dimensionless reflection locations, ζ  ≥ 0 ( ζ  = 0: the ODW reflects precisely at the expansion corner; ζ  > 0: the ODW reflects off the wall before the expansion corner). Two kinds of destabilization phenomena of the inviscid Mach reflection of an ODW induced by different mechanisms are found, namely wave-induced destabilization at large ζ  > 0 for moderate (not very low) Ma and inherent destabilization at any ζ  > 0 for low Ma . Wave-induced destabilization is attributed to the incompatibility between the pressure ratio across the Mach stem and its relative propagation speed, which is triggered by the action of the secondary reflected shock wave or the transmitted Mach stem on the subsonic zone behind the Mach stem. Inherent destabilization is demonstrated through an in-depth theoretical analysis and is attributed to geometric choking of the flow behind the Mach stem.